The Use of Distraction Osteogenesis for treatment of the mandibular deformity in hemi facial microsomia: A case report of the double osteotomy technique - R Krishna; S Kumar; A K Singh; S K Bhatnagar; V Kumar (Indian Journal of Plastic Surgery, 2001)
A patient presenting with hemi facial microsomia with Grade IIB mandibular deformity was treated by distraction osteogenesis after double osteotomy of the ramus and the body. A satisfactory facial symmetry was achieved following the surgery without any complications.